Strategy of effectiveness in the modern concept of reproductive health - V. V. Bobrytska (Publishing House TRILIST, 2017)
The modern concept of reproductive health is based not only on the search for optimal methods of treatment of diseases, preservation of planned pregnancy, prevention of maternal and child morbidity and mortality, but, first of all, on preventive correction of pathological conditions. These problems were examined on the 17th World Congress of the International Academy of Human Reproduction which took place on March 15-18, 2017 in Rome. In particular, the section "Current Problems in Reproductive Surgery" examined the problems of diagnosing pathological conditions before surgery, as well as issues of effective prevention of the disease recurrence. Within the framework of the section the associate professor of the Department of Perinatology, Obstetrics and Gynecology of the Kharkov Medical Academy of Postgraduate Education V.V. Bobritskaya presented the report "Management of patients after surgical treatment for ovarian neoplasia." The report described the results of data-analysis of the management of 140 patients after surgical treatment for benign ovarian tumors. A retrospective study of these results was presented: using combined oral contraceptives (COCs), combination of COCs and the metabolic oncoprotect drug Epigalin, as well as the results of the isolated use of Epigalin in the rehabilitation period (6-12 months). The aim of the study was to optimize the methods of preventing relapses of neoplastic processes in operated women of reproductive age. Among the observed patients, the best results were reported in the group receiving co-therapy COCs + Epigaline - no recurrence of ovarian neoplasia. In group I (COCs only) 1 case of the endometrioid cyst recurrence was observed, in group III (Epigalin only) - 1 case of the cyst of the yellow body recurrence. The expected maximum number of relapses (6) was observed in a group of women who did not take the recommended drugs during the rehabilitation period for various reasons. According to conclusion of the study authors, a combination of COCs with a low dose of 20 μg ethinyl estradiol and 150 μg desogestrel with 90 mg epigallocatechin-3-gallate and 400 mg indole-3-carbinol (Epigalin) can be considered as one of the optimal methods for preventing of ovarian neoplasia recurrence, and therapy of dyshormonal conditions. Preventative treatment must be performed in the postoperative period.